STUDY OF HUMAN REACTIONS THAN COLOR AND ITS EFFECTS ON ADVERTISING - Marzieh Talaei (International Journal of Accounting Research, 2013)
This paper aims to examine the impacts of the human psyche and subconscious color when buying and consuming goods Colors cannot be only from the physical perspective, But the psychological impact on the mechanism of color have human body through which can be used to predict many behaviors. Commerce and advertising can be valuable as an efficient tool and color in guiding the consumer interest and increase sales. This article shows to achieve cooler effects, in addition to knowledge of the psychological effects of color, as well as employing appropriate color in the advertisement with the space around and understand it’s symbolic, should study the culture and history of a country. And many of the behavioral patterns and the collective interests of the history and culture of a community identified. This article can be a better understanding of the psychological effects of color in the first phase of commercial advertising and to give to the fans